Asian journalism education and key challenges of climate change: A preliminary study - Maslog, Crispin (Pacific Journalism Review, 2017)
Commentary: The mass media in the Asia Pacific region are reporting the environmental disasters that are regularly hitting the planet religiously, and journalists learn as they go along. However, the reporting has focused mainly on the toll in human lives and property. This is disaster reporting and it stops short of contextualising. It does not adequately explain why the environmental disasters are happening more violently and more frequently. Not too many reporters have taken formal courses in environmental journalism. Only a very few schools are offering regular courses, or programmes in science and environmental reporting, as indicated by a mini-survey in July 2016. The vacuum in formal science and environmental education is being filled by non-government organisations offering non-formal training.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMjQxMzUvcGpyLnYyM2kxLjMxMg